Lipid Content and Productivity of Arthrospira platensis and Chlorella vulgaris under Mixotrophic Conditions and Salinity Stress - Teresa M. Mata (2016)
This study aims at evaluating the influence of mixotrophic growth and salinity stress in the lipid content and productivities of microalgae Arthrospira platensis (A. platensis) and Chlorella vulgaris (C. vulgaris). For comparison purposes, both microalgae were also cultivated in the standard autotrophic conditions: modified Zarrouk's medium for A. platensis and Bold's basal medium for C. vulgaris. The mixotrophic conditions were created by adding 1.00 g/L of glucose to their standard media, and the salt stress was induced by introducing sodium chloride (NaCl) in different amounts. As expected, the biomass concentration and productivity increases under mixotrophy but decreases with salinity stress. Therefore, although the lipid content increased with the salinity stress under mixotrophy, reaching maximum values of 15.4 and 23.0 % dry weight (dwt) respectively, for A. platensis (in 0.428 M of NaCl) and C. vulgaris (in 0.0214 M of NaCl), the biomass productivity reached minimum values. Consequently, the maximum biomass and lipid productivities were obtained with an intermedium lipid content and without the salinity stress. The maximum biomass and lipid productivities are 99.7 and 9.7 mg/L/day for A. platensis and 227.2, and 37.7 mg/L/day for C. vulgaris, respectively. This study also revealed that C. vulgaris adapts faster to salinity stress, whereas A. platensis is able to tolerate higher salinity concentrations.